The Impact of ESG disclosure and ESG Financial Materiality Disclosure on Financial Performance: Evidence from the Indonesian Energy Sector (2022–2024) - Yanti; Shandy Aurellia Renata (CV. Sakura Digital Nusantara, 2026)
Purpose – Sustainability reporting has become increasingly important in the energy sector due to growing regulatory requirements and stakeholder expectations. Nevertheless, evidence regarding the financial implications of ESG-related disclosures remains inconclusive. This study examines the impact of ESG disclosure and ESG financial materiality disclosure on the financial performance of energy companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024. Design/methodology/approach – This study employed a quantitative research design using panel data regression analysis. The sample comprised 19 energy sector companies selected through purposive sampling, resulting in 57 firm-year observations. ESG disclosure was measured based on the GRI Standards 2021, while ESG financial materiality disclosure was assessed using the SASB Materiality Framework. Data were analyzed using the Fixed Effect Model (FEM). Finding/Results – The results show that ESG disclosure is negatively associated with financial performance, although the relationship is not statistically significant. In contrast, ESG financial materiality disclosure has a negative and significant effect on financial performance, indicating that the costs associated with material ESG reporting may reduce short-term profitability. Originality/Value – The findings suggest that not all ESG-related disclosures generate similar financial outcomes. This study provides evidence that financially material ESG disclosure may have different implications from general ESG disclosure, offering insights for energy companies in designing sustainability reporting strategies.